A avaliação da qualidade do serviço dos centros de gestão, contabilidade e finanças do exército: uma proposta conforme o modelo SERVQUAL - Anelli, Ana Bordin (2023)
The present study aims to evaluate the quality of services provided by the Army Management, Accounting and Finance Centers (CGCFEx) from the point of view of the administration agents of the management units supported by them, based on a quantitative study carried out within the scope of action of the 7th CGCFEx (Army barracks that operates in the states of Pernambuco, Alagoas and Paraíba). To this end, a research instrument was developed based on the SERVQUAL methodology, which was applied to 294 administration agents. As results, it is obtained that there are mainly three aspects taken into consideration to identify whether the CGCFEx service is being well provided: response time to queries, technical aspects of the work and the way in which administration agents are treated. It was also identified that Senior Officers are more demanding and are more satisfied with the services provided by the 7th CGCFEx than the Senior Officers; that Experienced agents are more satisfied than Beginners; and those who have worked for more than 9 years are more satisfied than those who have worked for less than 2 years.